Factors that Influence the Health Levels of Saving and Loan Cooperatives (KSP)/ Saving and Loan Unit (USP) Cooperatives in North Jakarta, Indonesia - Endro Praponco (Enrichment : Journal of Management, 2022)
This study examines factors (Capital, Quality of Production Asset, Management, Efficiency, Liquidity, Independence & Growth, Cooperative Identity) that influence the health levels of Savings and Loans Cooperatives (KSP)/ Savings and Loans Unit (USP) Cooperatives in North Jakarta, Jakarta Indonesia. In North Jakarta, Health Assessment program for KSP and USP Cooperative existed and has been operational, and thus, they are qualified to carry out health assessment activities. The data used in this study are primary data and secondary data. The Primary data is the respondent's answers concerning issues related to institutional, finance and management aspects. The Secondary data is data from KSP / USP annual report and data from related instances from the Departement of SMEs and Trade Cooperative of North Jakarta. The analysis technique used in descriptive analysis in order to determine the level of soundness of 30 KSP and USP Cooperatives in North Jakarta. The analysis showed that: 1) The overall level of health of KSP / USP Cooperative in North Jakarta on 30. KSP/USP cooperative sampled in this study, in terms of capital, quality of production asset, management, efficiency, liquidity, independence & growth, cooperative identity, an resulting into healthy and reasonably healthy status. 2) Simultaneously capital, productivity, asset quality, management, efficiency, liquidity, Independence & growth, cooperative identity variables have significant effect on the soundness of the KSP / USP Cooperative in North Jakarta with a coefficient of determination (R2) = 99.6%. 3) Individually, capital, production, asset quality, management, efficiency, liquidity, independence & growth, cooperative identity variables have positive and significant impact on the level of soundness of KSP / USP cooperatives in North Jakarta. 4) Finally, production, asset quality, liquidity, independence & growth are the dominant variables that affect the level of soundness of KSP / USP cooperativse in North Jakarta.